Directly Observed Treatment for Iron Tablet Supplements Consumption Among Female Senior High School Students (KEMAS: Jurnal Kesehatan Masyarakat, 2023)
Anemia is one of the reproductive health problems in adolescents. The incidence of anemia is still high in Indonesia. Supplementation of Iron tablets per week is one of the policies to decrease the anemia incident. This study aims to determine the effectiveness of the implementation of Directly Observed Treatment (DOT) for Iron Tablet Supplements. Consumption was observed in high school students for 12 weeks. This study was a quantitative study with a quasi-experimental design, with the experiment group being peers as DOT and the control group being guidance counseling teachers. This research was conducted from July to October 2019 in Sleman and Bantul. Samples used for both groups were 70 respondents. Data analysis used univariate and bivariate. The results of this study showed that the incidence of anemia for both groups was still high at 51.4% before giving the iron tablets to 34.3% after the tablets were given. The implementation of DOT in the consumption of iron tablets in the teacher group showed non-adherence to drinking iron tablet only 2.9% and by peers up to 31.4%. Observed by the teacher showed an effect on the difference in Hemoglobin levels before and after treatment with p=0.037 and peer as observed with p=0.247.